PENANGGULANGAN TINDAK PIDANA YANG DILAKUKAN OLEH WANITA DALAM PEREDARAN NARKOTIKA: (Studi di Polres Demak) - Arifin; Wibawa, Iskandar (Veteran Law Review, 2023)
Based on data from the Demak Detective Police in 2023, it appears that there is a decrease in female suspects who are narcotics cases at the Demak Police Station, indicating that the prevention measures are optimal, but on the other hand it needs to be analyzed whether it has been optimally carried out by law enforcers and whether it is due to the imposition of penalties on users and dealers who are appropriate, or because of special guidance / handling. The research method used is empirical juridical legal research. The results of the research of Demak Police have carried out the right criminal law policy, which includes what actions should be made a criminal offense and what sanctions should be given to the violator. So it can be concluded that law enforcement against narcotics crimes committed by women in the Demak Police jurisdiction, namely First, is to start from preventive measures (preventive) and secondly by repressive means if the preventive method is unsuccessful which is the core of the duties and authority of the police as law enforcers in their capacity as investigators. And there is no difference (all the same) law enforcement between abuse committed by men or women, both dealers, dealers / couriers and users, but the same treatment in terms of investigation. The only difference is when the search of the female body is carried out by the female police.